Determining implementation issues of open notes in primary care: a focus group study - Marianne Dees; Sevde Alkir-Yurt; Gert Olthuis; Jozé Braspenning (BMC Primary Care)
Abstract Background In several countries, patients have online access to medical records (open notes) contributing to patient engagement and healthcare outcomes. However, usage is still low. Healthcare professionals’ viewpoints on open notes are under-represented in existing reviews. And a systematic framework to understand the implementation is lacking. Using the ‘capability approach’, we evaluated the value of open notes by examining influencing factors and capabilities (opportunities and challenges) of patients and staff in general practices. Method Qualitative research was conducted in 10 Dutch general practices (19 healthcare professionals and 29 patients) that were included through purposive sampling aiming at a diversity of practices and patients. Three focus groups were held with primary care staff and 10 with patients, led by an experienced facilitator using a topic guide. Content analysis was used for the transcripts of the focus groups; coded in ATLAS.ti in three rounds by two researchers independently. The results were discussed with the research team to identify factors and capabilities that could affect the usability of open notes. Results Personal, social, and environmental factors appeared to influence the use of open notes, such as digital and health literacy, social support from and within the practice, and legislation and regulation. Patients and healthcare professionals agreed on most of these factors. From the capabilities, four implementation themes were identified. First, ambiguity about ownership of medical records and concerns about data integrity should be addressed. Second, the change in practice organization and the care process caused by open notes need practical support. Third, fear of the unknown and unintended consequences of open notes must be considered. Fourth, the introduced change to the healthcare professional-patient relationship requires additional skills. These themes applied to both patients and healthcare professionals, but the differences became clear in the details. Conclusion The study provides insight into how patients and healthcare professionals experience open notes. Besides the practical barriers and facilitators, patients and healthcare professionals addressed four implementation themes that should guide the further implementation of open notes to improve patient engagement and health outcomes.